Comparison of the Clinical Value of miRNAs and Conventional Biomarkers in AMI: A Systematic Review - Wang, Baofu; Li, Yang; Hao, Xuezeng; Yang, Jingjing; Han, Xiaowan; Li, Haiyan; Li, Tong; Wang, Dayang; Teng, Yu; Ma, Liang; Li, Yao; Zhao, Mingjing; et al. (Frontiers in Genetics, 2021)
Background/Aims: This study aimed to compare the clinical value of the peak time point and area under the curve (AUC) of miRNAs and conventional biomarkers in acute myocardial infarction (AMI). Methods: A literature search was carried out in PubMed, Web of Science, Embase, and Cochrane systematically. Screening studies, extracting data, and assessing article quality were performed independently by two researchers. Also, the names of miRNAs in the included studies were standardized by the miRBase database. Results: A total of 40 studies, encompassing 6,960 participants, were included in this systematic review. The samples of circulating miRNAs were mainly from the plasma. The results of this systematic review displayed that miR-1-3p, miR-19b-3p, miR-22-5p, miR-122-5p, miR-124-3p, miR-133a/b, miR-134-5p, miR-150-5p, miR-186-5p, miR-208a, miR-223-3p, miR-483-5p, and miR-499a-5p reached peak time earlier and showed a shorter time window than the conventional biomarkers despite the different collection times of initial blood samples. miR-1-3p, miR-19b-3p, miR-133a/b, miR-208a/b, miR-223-3p, miR-483-5p, and miR-499a-5p were shown to be more valuable than classical biomarkers for the early diagnosis of AMI, and these miRNAs appeared to have the most potential biomarkers within 4 h of the onset of symptoms except miR-133a/b and miR-208b. Moreover, combined miRNAs or miRNAs combined with classical biomarkers could compensate for the deficiency of single miRNA and conventional biomarker in sensitivity or specificity for an optimal clinical value. Conclusions: miR-1-3p, miR-19b-3p, miR-208a, miR-223-3p, miR-483-5p, and miR-499a-5p are promising biomarkers for AMI due to their satisfactory diagnostic accuracy and short time window (within 4 h of the onset of symptoms).